MEASURING TOOL DESIGN AC POWER MICROCONTROLLER ATMEGA8535 - hilman hermawan jufri (Saintia Fisika, 2013)
The electric power gauge has been made based digital power metre AVR microcontroller ATMega 8535 using current sensor in the from of  ACS 712 a number of 5 amperes grading DC voltage,microcontroller AVR ATMega 8535 with ADC(Analog to Digital Converter) in it, and also using LCD 2 x 16 characters it can measure and display the electrical power of a household electronic appliances. ACS 712 current sensor with a maximum output a number of 5 amperes and server to detect AC current flowing in the load and provide AC voltage output which is then converted into DC voltage. Internal ADC microcontroller AVR ATMega 8535 server to convert the output voltage of current sensor into digital data then can be processed and displayed on the LCD. The series of minimum system microcontroller AVR ATMega 8535 and the LCD display are controlled by a program that is created through AVR studio software using the downloader ISP for AVR ATMega 8535. Based on the testing and calibration that has been done to measure the electric obtained an average yield of 4.3214% percentage error rate measurement accuracy of 95.67%.